PENGARUH FINANCIAL LITERACY, FINANCIAL EXPERIENCE, DAN FINTECH TERHADAP FINANCIAL BEHAVIOR MASYARAKAT KOTA DEPOK - Farah Salsabila Putri Waluyo; Arif Widodo Nugroho; Deni Adha Akbari (Creative Research Management Journal, 2023)
This study aims to find out how the influence of financial literacy, financial experience, and financial technology (fintech) on financial behavior in Depok City. In this study using a quantitative approach. The data source in this study uses primary data by collecting data through questionnaires distributed to people in Depok City who use e-payments. The sampling technique in this study was using purposive sampling, so the number of samples in this study was 210 respondents. As for the data analysis technique in this study using Partial Least Square (PLS) with the help of SmartPLS 4 for windows. The results of this study indicate that financial literacy and financial technology have a positive and significant impact on financial behavior among e-payment users in Depok City. As for financial experience, it has no influence on financial behavior. This can happen because when people in Depok City make payments, they are still not careful in deciding their finances and they have different characteristics.